Implementation of Data Security with Wallace Tree Approach Using Elliptical Curve Cryptography on FPGA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The growth of computing resources and parallel computing has led to significant needs for efficient cryptosystems over the last decade. Elliptic Curve Cryptography (ECC) provides faster computation over other asymmetric cryptosystems such as RSA and greater security. For many cryptography operations, ECC can be used: hidden key exchange, message encryption, and digital signature. There is thus a trade-off between safety and efficiency with regard to speed, area and power requirements. This paper provides a good ECC approach to encryption by replacing the Vedic multiplier (16 bit) with the Wallace tree multiplier with an improved output (128 bit). The proposed design processes data recurringly with less volume, less power consumption and greater velocity, in addition to improving efficiency. Using Xilinx 2015.2 software, the entire proposed design is synthesized and simulated and implemented on the ZYNQ FPGA Board. Compared with previous implementations, a significant improvement in field efficiency, time complexity and energy demand is demonstrated by the proposed design.